Improving Electrochemical Stability and Low‐Temperature Performance with Water/Acetonitrile Hybrid Electrolytes. Issue 3 (22nd November 2019) - Chen, Jiawei; Vatamanu, Jenel; Xing, Lidan; Borodin, Oleg; Chen, Huiyang; Guan, Xiongcong; Liu, Xiang; Xu, Kang; Li, Weishan
Abstract: Although the "water‐in‐salt" electrolyte has significantly expanded the electrochemical stability window of aqueous electrolytes from 1.23 to 3 V, its inevitable hydrogen evolution under 1.9 V versus Li + /Li prevents the practical use of many energy‐dense anodes. Meanwhile, its liquidus temperature at 17 °C restricts its application below ambient temperatures. An advanced hybrid electrolyte is proposed in this work by introducing acetonitrile (AN) as co‐solvent, which minimizes the presence of interfacial water at the negatively charged electrode surface, and generates a thin and uniform interphase consisting of an organic outer layer based on nitrile (CN) and sulfamide (R‐S‐N‐S) species and an inner layer rich in LiF. Such an interphase significantly suppresses water reduction and expands the electrochemical stability window to an unprecedented width of 4.5 V. Thanks to the low freezing point (−48 °C) and low viscosity of AN, the hybrid electrolyte is highly conductive in a wide temperature range, and enables a LiMn2 O4 /Li4 Ti5 O12 full cell at both ambient and sub‐ambient temperatures with excellent cycling stability and rate capability. Meanwhile, such a hybrid electrolyte also inherits the nonflammable nature of aqueous electrolyte. The well‐balanced merits of the developed electrolyte make it suitable for high energy density aqueous batteries. Abstract : Aqueous lithium‐ion batteries suffer from a narrow electrochemical stability window and poor low‐temperature performance due to the nature of water. These issues can be solved by introducing a nonaqueous solvent, acetonitrile. Such a water/acetonitrile hybrid electrolyte expands electrochemical stability window to an unprecedented width of 4.5 V and enables Li4 Ti5 O12 anode‐based batteries with excellent cycling stability, rate capability, and low‐temperature performance.